Statistical meta-analysis with applications - Hartung, Joachim, Prof. Dr.; Knapp, Guido; Sinha, Bimal K., 1946- (Hoboken, N.J. : Wiley, 2008)
"Statistical Meta-Analysis with Applications presents the necessary statistical methodologies that allow readers to tackle the four main stages of meta-analysis: problem formulation, data collection, data evaluation, and data analysis and interpretation. Combining the authors' expertise on the topic with a wealth of up-to-date information, this book successfully introduces the essential statistical practices for making thorough and accurate discoveries across a wide array of diverse fields, such as business, public health, biostatistics, and environmental studies."--Jacket.
Introduction -- Various measures of effect size -- Combining independent tests -- Methods of combining effect sizes -- Inference about a common mean of several univariate normal populations -- Tests of homogeneity in meta-analysis -- One-way random effects model -- Combining controlled trials with normal outcomes -- Combining controlled trials with discrete outcomes -- Meta-regression -- Multivariate meta-analysis -- Bayesian meta-analysis -- Publication bias -- 14. Recovery of inter-block information -- Combination of polls -- Vote counting procedures -- Computational aspects data sets.
Includes bibliographical references and index.
Keywords: Statistical hypothesis testing; Meta-analysis.; Meta-Analysis as Topic; Data Interpretation, Statistical; Statistics as Topic -- methods